Cerebral Abscess Potentially of Odontogenic Origin - Ben Hadj Hassine, Marouene (Case Rep Dent, 2015)
Odontogenic origins are rarely implicated in the formation of brain abscesses. The relative paucity of this kind of infection and the difficulty in matching the causative microorganisms of a brain abscess to an odontogenic source can explain the late management of patients. We herein describe a case of a 46-year-old man with a cerebellar abscess that was probably due to an odontogenic infection. The diagnosis supported by imaging and microscopic identification, mini craniectomy for abscess drainage followed by eradication of all potential dental infectious foci, and an antibiotic regimen based on cephalosporins, metronidazole, and vancomycine contributed to a successful outcome.